Step brothers [videorecording (DVD)] - McKay, Adam, 1968-; Ferrell, Will, 1967-; Ferrell, Will, 1967-; Reilly, John C., 1965-; Reilly, John C., 1965-; Jenkins, Richard, 1947-; Steenburgen, Mary; Scott, Adam, 1973-; Hahn, Kathryn, 1974-; Riggle, Rob; Savage, Andrea, 1973-
When Nancy and Robert marry, their slacker sons struggle to get along and get employed.